Legal Consequences of Land Rights Conversion and Recognition of Customary Rights in Land Registration - Kuahaty, Sarah Selfina; Berlianty, Teng; Dyastuti, Risqi Mumpuni; Sinaga, Roulinta Yesvery (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article analyzes the legal consequences of land conversion and the registration of customary land in Indonesia, as stipulated by Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Apartment Units and Land Registration. Many communities maintain traditional understandings of land ownership, which often differ from formal legal recognition. Purposes of the Research: This research aims to determine the legal ramifications of failing to register land rights, particularly conversion rights and customary lands, within the prescribed timeframe. Methods of the Research: This research was conducted using a normative juridical method. The approaches used are the legislative approach and the conceptual approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. The legal processing technique used is to process legal materials by systematizing and the analysis of legal materials is qualitative in nature by interpreting legal materials and providing conclusions using deductive methods from real problems on legal issues. Results Main Findings of the Research: The findings indicate that delayed registration under Government Regulation Number 18/2021 renders old proof of ownership invalid, potentially leading to the land becoming state land. This has significant implications for legal certainty, formal recognition of ownership, protection against rights loss, and administrative consequences for individuals and communities. The research highlights the critical importance of timely registration to secure land rights and emphasizes the need for policies that protect indigenous communities and facilitate access to the registration process.